2012
DOI: 10.3109/08958378.2012.691913
|View full text |Cite
|
Sign up to set email alerts
|

Health effects research and regulation of diesel exhaust: an historical overview focused on lung cancer risk

Abstract: The mutagenicity of organic solvent extracts from diesel exhaust particulate (DEP), first noted more than 55 years ago, initiated an avalanche of diesel exhaust (DE) health effects research that now totals more than 6000 published studies. Despite an extensive body of results, scientific debate continues regarding the nature of the lung cancer risk posed by inhalation of occupational and environmental DE, with much of the debate focused on DEP. Decades of scientific scrutiny and increasingly stringent regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 192 publications
(439 reference statements)
0
42
0
1
Order By: Relevance
“…More than 5000 different compounds including heterogeneous mixtures of gases, uncondensed vapors and particulate matter containing many different aromatic amines, carbonyls, phenolics, polycyclic aromatic hydrocarbons (PAHs), nitroaromatics, nitroheterocyclics, inorganics, organics, volatile hydrocarbons, metals, aldehydes, ketones, etc. have been identified during combustion processes (Hesterberg et al, 2012;Prasad andBella, 2010 Zhang andTao, 2009;Ravindra et al, 2008;Venkatachari et al, 2007;Donaldson et al, 2005). Common human pathological effects of these toxicants include direct oxidation of biomolecules, generation of free radicals, induction of the inflammatory response system (Kampa and Castanas, 2008) and interference with signaling pathways (Valko et al, 2006;Hesterberg et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…More than 5000 different compounds including heterogeneous mixtures of gases, uncondensed vapors and particulate matter containing many different aromatic amines, carbonyls, phenolics, polycyclic aromatic hydrocarbons (PAHs), nitroaromatics, nitroheterocyclics, inorganics, organics, volatile hydrocarbons, metals, aldehydes, ketones, etc. have been identified during combustion processes (Hesterberg et al, 2012;Prasad andBella, 2010 Zhang andTao, 2009;Ravindra et al, 2008;Venkatachari et al, 2007;Donaldson et al, 2005). Common human pathological effects of these toxicants include direct oxidation of biomolecules, generation of free radicals, induction of the inflammatory response system (Kampa and Castanas, 2008) and interference with signaling pathways (Valko et al, 2006;Hesterberg et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…The diversity of these products is huge, and their estimated number may be as high as several thousand different chemical compounds occurring as gas or in the form of solid particles. The basic gaseous components of exhaust fumes emitted by compression-ignition (diesel) engines are: carbon oxides, nitrogen and its compounds, oxygen, steam, sulfur IJOMEH 2016;29(4) 669 cancer [1,6,13]. In 2012, the International Agency for Research on Cancer (IARC) classified diesel exhaust fumes as carcinogenic to humans (group 1 of IARC classification).…”
Section: Introductionmentioning
confidence: 99%
“…[5] For both DEPs and WSPs, variations in the organic fraction composition have been reported, depending on the fuel type and combustion conditions. [6,7] Several studies have indicated that the organic fraction of combustion PM is responsible for the toxicological effects. [8][9][10][11][12][13][14][15] We recently compared the potency of native DEPs, their corresponding methanol extracts and residual particles to induce expression of multiple pro-inflammatory linked genes in human bronchial epithelial cells.…”
Section: Introductionmentioning
confidence: 99%